2018
DOI: 10.1029/2018je005604
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Swirl Morphology Constrains the Geometry, Magnetization, and Origins of Lunar Magnetic Anomalies

Abstract: Lunar swirls are collections of finely structured bright and dark surface markings, alternating over length scales of typically 1-5 km. If swirls are the result of plasma interactions with crustal magnetic anomalies or electrostatic or magnetic sorting of fine materials, the magnetic field orientation must vary over similar length scales. This requires that the associated source bodies be both shallow and narrow in horizontal extent. The correspondingly restricted volume of the source bodies in turn implies st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 81 publications
2
62
0
Order By: Relevance
“…Both the SPA ejecta and the younger basin ejecta models have an advantage in that the susceptibility of metallic iron‐enriched ejecta to TRM is orders of magnitude larger than that of typical lunar igneous rocks such as mare basalt (Weiss & Tikoo, ). On the other hand, Hemingway and Tikoo () have recently proposed that, under favorable conditions (high‐temperature magmas in a highly reducing environment), dikes or lava tubes with thicknesses >1 km could acquire magnetization intensities consistent with observed magnetic anomaly amplitudes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Both the SPA ejecta and the younger basin ejecta models have an advantage in that the susceptibility of metallic iron‐enriched ejecta to TRM is orders of magnitude larger than that of typical lunar igneous rocks such as mare basalt (Weiss & Tikoo, ). On the other hand, Hemingway and Tikoo () have recently proposed that, under favorable conditions (high‐temperature magmas in a highly reducing environment), dikes or lava tubes with thicknesses >1 km could acquire magnetization intensities consistent with observed magnetic anomaly amplitudes.…”
Section: Discussionmentioning
confidence: 96%
“…Some groups have suggested igneous sources of lunar anomalies consisting of vertical tabular (dike) intrusions (Hemingway & Tikoo, 2018;Purucker et al, 2012;Tsunakawa et al, 2014Tsunakawa et al, , 2015 while other groups have suggested sources in the form of impact basin ejecta deposits (Hood et al, 2013;Wieczorek et al, 2012). Analyses of Apollo samples found that impact melt rocks originating from large basin-forming impacts contain enhanced metallic iron abundances (1-2 wt %) that were apparently derived from the impactors that formed the basins (Haskin et al, 1998;Korotev, 1994Korotev, , 2000.…”
Section: Possible Origins Of Crater-associated Anomaliesmentioning
confidence: 99%
“…Furthermore, the disk model is more physically plausible than linear structures. Intrusive bodies or lava tubes, which are candidates for producing linear magnetic anomalies (Hemingway & Tikoo, 2018), would not typically have the high degree of symmetry and ellipticity observed in the optical pattern. In contrast, two-dimensional circular or elliptical features are ubiquitous on the Moon in the form of craters.…”
Section: Improvements Of the Disk Modelmentioning
confidence: 99%
“…In particular, researchers have suggested that the Reiner Gamma anomaly may be ejecta from the Cavalerius (Hood et al, 1979a) or Imbrium impacts ; the latter supported by the possible orientation of Reiner Gamma optical pattern toward Imbrium), although they did not model these processes in detail. Other studies suggest that volcanic processes may be responsible (Hemingway & Tikoo, 2018;Purucker et al, 2012), and there is still the possibility that some were magnetized by plasma-amplified magnetic fields (Hood & Artemieva, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation